2017
DOI: 10.1080/14767058.2016.1276558
|View full text |Cite
|
Sign up to set email alerts
|

Type-2 diabetes mellitus: does prenatal care affect outcomes?

Abstract: Treatment of T2DM throughout pregnancy leads to improved maternal and neonatal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 9 publications
1
30
0
Order By: Relevance
“…It is worth highlighting that adequate prenatal care is associated with more favorable outcomes in maternal and infant health, especially when the prenatal care group included a multidisciplinary team. 26,27 The multivariate analysis also showed statistically significant association between age and long birth intervals. Age < 20 years old decreases the chances of long birth intervals, whereas age !…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…It is worth highlighting that adequate prenatal care is associated with more favorable outcomes in maternal and infant health, especially when the prenatal care group included a multidisciplinary team. 26,27 The multivariate analysis also showed statistically significant association between age and long birth intervals. Age < 20 years old decreases the chances of long birth intervals, whereas age !…”
Section: Discussionmentioning
confidence: 70%
“…A possible explanation for this finding is the potential of prenatal care in monitoring gestational morbidities. 26 No association was found between prevalence of anemia during pregnancy and birth interval. Despite the fact that anemia is common during pregnancy, the findings in the literature are inconclusive.…”
Section: Discussionmentioning
confidence: 97%
“…Pre‐pregnancy counseling results in better metabolic control at conception and has been linked to better outcomes for women with type 1 and type 2 diabetes: higher rates of stillbirth and preterm delivery have been reported among women who booked late . Mean HbA1c was almost 1% lower in a British cohort than in the present study, which also demonstrated higher rates of congenital anomalies, highlighting the relevance of preconception care.…”
Section: Discussionmentioning
confidence: 40%
“…Pre-pregnancy counseling results in better metabolic control at conception and has been linked to better outcomes for women with type 1 23 and type 2 diabetes: higher rates of stillbirth and preterm delivery have been reported among women who booked late. 24…”
Section: Discussionmentioning
confidence: 99%
“…Wei et al 18 also reported that the risk of PTB was higher in women who had pre-gestational diabetes mellitus (OR = 1.17, 95% CI: 1.14-1.20; P < 0.001), after a retrospective study of 6447339 Chinese pregnant women who participated in prenatal care. Allison et al 19 also revealed that PTB was statistically signi cant with AOR 1.55 (95% CI: 1.03-2.32) in women with type-2 diabetes mellitus. They found that women who did not present for prenatal care until time of delivery had an increased risk of stillbirth and PTB which pointed out the indispensable necessity of routine prenatal care.…”
Section: Validation Of Scoring Systemmentioning
confidence: 93%